Pemikiran Teologi Muhammadiyah Dalam Himpunan Putusan Tarjih - Akbar Muhadist (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2021)
Islamic theology is an important part of the intellectual heritage left by classical Muslim thinkers. Directly or indirectly, Islamic theology has become the spirit for all pulses of Islamic thought, whether political, social, or economic. Muhammadiyah certainly needs to be recognized and understood from its various aspects that are inherent in the identity of this Islamic movement. Muhammadiyah is an Islamic movement that was founded in Yogyakarta on November 18, 1912 Miladiyah or 8 Dzulhijjah 1330 Hijriyah with the founder Kiai Haji Ahmad Dahlan. Muhammadiyah is considered as the largest Islamic organization in Indonesia. With its age that has passed a century, it has become a very large Islamic organization in Indonesia. Muhammadiyah is even known as the largest modern Islamic organization not only in Indonesia but throughout the world. The sources of data in this study include primary data and secondary data. Primary data sources are data directly collected from the books of the Tarjih Judgment Association, while secondary sources are from books, scientific journals, magazines, documents and papers related to this research topic as supporting data for primary data sources, and according to the type This research is library research, so the research data collected, both primary data and secondary data obtained from books, scientific journals, magazines, documents and other papers are read and analyzed for their contents. The data of the findings are disclosed descriptively and objectively and described through the inductive method. The theological thought of Muhammadiyah in the Tarjih Judgment Association is that Muhammadiyah uses the word ahlul haq wassunnah (Ahli Sunnah/Asy'ariyah). According to Muhammadiyah, Allah has a great name, Allah also has a qadim dzatiyyah character. Muhammadiyah chooses the opinion which says that Allah's name is taufiqi. As the Sunnah Experts argue that the nature of Allah is also taufiqi. Both can only be known through the sam'i argument as stated in the holy book or the sunnah of the Prophet. Muhammadiyah also does not recognize tri-tawhid (uluhiyyah, rububiyyah, and asthma' wa sifat). According to the Muhammadiyah understanding as stated in the HPT and also the Sunnah of the Asy'ariyah sect, that there is only one monotheism. Uluhiyah, essence and nature are an inseparable unit. Separating the three can invalidate monotheism.